Technology, pedagogy, and content knowledge in mathematics education: a systematic literature review - Hanifah, Umi; Budayasa, I Ketut; Sulaiman, Raden (Intelektual Pustaka Media Utama, 2025)
This literature review examines how mathematics education uses the Technology, pedagogy, and content knowledge (TPACK). This study examines how TPACK affects mathematics classroom instruction, student engagement, and learning outcomes. A detailed examination and synthesis of pertinent publications over the last decade will accomplish this. The study illuminates significant topics, including digital technology utilization, teacher professional development program enhancement, and TPACK acceptability. It also highlights long-standing issues such as limited technology budgets, teacher training issues, and the need for ongoing support. This post provides current ideas and a full literature review to assist us in understanding TPACK. The findings impact educational policymakers, teacher professional development programs, and math teachers. The paper then advises future research. One is a longitudinal study of different educational environments to determine long-term effects on teaching and student growth. Policymakers, educators, and academics can utilize this study review to advocate for acceptable technology usage in mathematics education.